A house in the mountains : the women who liberated Italy from fascism - Moorehead, Caroline (London: Chatto &Windus, 2019)
In the late summer of 1943, when Italy broke with the Germans and joined the Allies after suffering catastrophic military losses, an Italian Resistance was born. Four young Piedmontese women, Ada, Frida, Silvia and Bianca, living secretly in the mountains surrounding Turin, risked their lives to overthrow Italy's authoritarian government. They were among the thousands of Italians who joined the Partisan effort to help the Allies liberate their country from the German invaders and their Fascist collaborators. What made this partisan war all the more extraordinary was the number of women like this brave quartet who swelled its ranks.
Part one: The fall of Italy. A Roman coup -- Interlude -- Bursting into life -- A war zone -- Making lions -- The piccoli geni -- A little woman -- Part two: A year of fire. Heedless -- The hunters and the hunted -- A lizard among the rocks -- Nesting in kitchens -- Summer of flames -- Haunted by death -- Learning to live better -- Part three: Liberation. Mothers of the resistance -- Squashing the cockroaches -- Insurrection -- Bloodletting -- A love of forgetting.
"Originally published in Great Britain in 2019 by Chatto & Windus, an imprint of Vintage."--Title page verso.
Includes bibliographical references (pages 353-362) and index.
Keywords: 1939-1945; World War, 1939-1945 -- Underground movements -- Italy; Italy -- History -- German occupation, 1943-1945.; Italy; Biographies; History; Biographies